Isolation of nb2se9 molecular chain from bulk one-dimensional crystal by liquid exfoliation - Chae, Sudong; Siddiqa, Akhtar J.; Oh, Seungbae; Kim, Bum Jun; Choi, Kyung Hwan; Jang, Woo Sung; Kim, Young Min; Yu, Hak Ki; Choi, Jae Young (Nanomaterials, 2018)
The optimum solvent for Nb2Se9 dispersion, which is a new type of one dimensional (1D) material, is investigated. Among several solvents (16 solvents in total), strong dispersion was observed in benzyl alcohol, isopropyl alcohol, isobutyl alcohol, and diacetone alcohol, which have medium dielectric constants in the range of 10 to 30 and surface tension in the range of 25 to 35 mJ m−2 . 1D Nb2Se9 chains, whose size is less than 10 nm, are well dispersed and it is possible to disperse mono-chains of 1 nm or less in a specific dispersion region. The 1D unit chain with dangling bond free surface and high volume to area ratio is expected to be used in applications that utilize the surface of the material. Such dispersion is an important first step towards various potential applications and is an indispensable scientific goal for the practical applications of Nb2Se9 .
Keywords: 1d materials; Liquid exfoliation; Nb2se9; Solvent dispersion